2021
DOI: 10.3390/molecules26165066
|View full text |Cite
|
Sign up to set email alerts
|

A Simple HPLC/DAD Method Validation for the Quantification of Malondialdehyde in Rodent’s Brain

Abstract: In the present study, a HPLC/DAD method was set up to allow for the determination and quantification of malondialdehyde (MDA) in the brain of rodents (rats). Chromatographic separation was achieved on Supelcosil LC-18 (3 μm) SUPELCO Column 3.3 cm × 4.6 mm and Supelco Column Saver 0.5 μm filter by using a mobile phase acetonitrile (A) and phosphate buffer (20 mM, pH = 6) (B). Isocratic elution was 14% for (A) and 86% for (B). The injection volume (loop mode) was 100 μL with an analysis time of 1.5 min. Flow rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Following the heating process, the samples were transferred in HPLC vials and promptly analyzed following the derivatization reaction. For the analysis of plasma samples, a similar procedure was followed, with strict modifications [ 56 ]. Representative chromatograms of plasma and brain MDA analysis are shown in Supplementary Figures S1 and S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Following the heating process, the samples were transferred in HPLC vials and promptly analyzed following the derivatization reaction. For the analysis of plasma samples, a similar procedure was followed, with strict modifications [ 56 ]. Representative chromatograms of plasma and brain MDA analysis are shown in Supplementary Figures S1 and S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Так, деякими вченими зареєстровано, що при стресі вміст продуктів перекисного окиснення ліпідів зростає: концентрація дієнових кон'югатів на 10,6%, а МДА -на 11,7% [22]. Отримані в ході інших досліджень аналітичні кореляційні криві для МДА в головному мозку також були лінійними, а концентрація перебувала в нормальному діапазоні (0,2-20 мкг/г, коефіцієнт регресії =0,998) [23].…”
Section: параметрunclassified
“…This decrease in GSH is most likely due to methanol metabolites. In fact, multiple studies have demonstrated this oxidative damage, both at the hepatocellular level and in the kidneys, but, most likely, there are oxidative lesions at the central level as well [ 142 , 145 , 146 , 147 , 148 , 149 ]. In the same manner, a reduction in protein thiols was observed, which resulted from the oxidation of thiolic groups (-SH), which was the result of the decrease in GSH [ 142 , 145 ].…”
Section: From Pure Caffeine To Coffee Productsmentioning
confidence: 99%